Technical skills predictive of winning at CEV Volleyball Men`s Champions League: identification and importance - Patsiaouras, A.; Kokaridas, D. (Trends in Sport Sciences, 2019)
The purpose of the study was to determine the technical elements leading to a prediction of winning or losinga volleyball match during theEuropean Volleyball Confederation (CEV) men`s volleyball championships in 2018. Material and Methods. The sample consisted of all men teams` matches of the CEV Volleyball Champions League during 2018 season. The differences in technical elements between the teams were recorded. Seventy-six matches were evaluated using the official statistical logistic package of the European Confederation (CEV), as well as the SPSS 21 statistical package for additional analysis. Discriminant analysis was used to find which measured variables significantly contributed to the prediction of winning or losing a match, helped teams to progress successfully throughout the tournament, and led the best teams to the Final Four round. Results and Conclusions. Results showed that "serve total", "reception total", "attack excellent", and "block" led to the prediction of the match outcome (winning or losing a match), whereas "serve error", "reception excellent" emerged as the decisive factors for team`s qualification, and finally "attack positive" was the only factor that could lead men`s teams to participate in the CEV Final Four round.